Penerapan Sistem Teknologi Informasi dalam Mendukung Monitoring Ketersediaan Fasilitas Perumahan Dinas TNI Angkatan Laut - Wawan Eko Rudi Cahyono (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study discusses the implementation of an information technology system to support the monitoring of the availability of Navy housing facilities. The method used in this research is qualitative, involving observation, interviews, and data analysis to understand the needs and challenges faced in managing housing facilities. The primary objective of this study is to design and implement an information technology system that can improve efficiency and accuracy in monitoring housing availability and support more effective decision-making. The results show that the developed system can provide real-time information on availability status, condition, and utilization of housing facilities. With this system, the administrative process becomes more structured and transparent, and data management errors are reduced. This research is expected to serve as a reference for developing similar systems in other military institutions.